A model for evaluating the biomechanics of rib fracture fixation. (December 2020) - Myers, Devon M.; McGowan, Sean P.; Taylor, Benjamin C.; Sharpe, B. Dale; Icke, Kyle J.; Gandhi, Anup
Abstract: Introduction: High rates of morbidity and mortality following flail chest rib fractures are well publicized. Standard of care has been supportive mechanical ventilation, but serious complications have been reported. Internal rib fixation has shown improvements in pulmonary function, clinical outcomes, and decreased mortality. The goal of this study was to provide a model defining the biomechanical benefits of internal rib fixation. Methods: One human cadaver was prepared with an actuator providing anteroposterior forces to the thorax and rib motion sensors to define interfragmentary motion. Cadaveric model was validated using a prior study which defined costovertebral motion to create a protocol using similar technology and procedure. Ribs 4–6 were fixed with motion sensors anteriorly, laterally and posteriorly. Motion was recorded with ribs intact before osteotomizing each rib anteriorly and laterally. Flail chest motion was record with fractures subsequently plated and analyzed. Motion was recorded in the sagittal, coronal and transverse axes. Findings: Compared to the intact rib model, the flail chest model demonstrated an 11.3 times increase in sagittal plane motion, which was reduced to 2.1 times the intact model with rib plating. Coronal and sagittal plane models also saw increases of 9.7 and 5.1 times, respectively, with regards to flail chest motion. Both were reduced to 1.2 times the intact model after rib plating. Interpretation: This study allows quantification of altered ribcage biomechanics after flail chest injuries and suggests rib plating is useful in restoring biomechanics as well as contributing to improving pulmonary function and clinical outcomes. Highlights: We describe a biomechanical model of rib motion allowing quantification of flail segment motion. Flail chest model shows increased rib segment motion in all planes, highest in the sagittal plane. Rib plating decreased motion at the fractured flail chest segment to within a normal range.